Synthesis of 2-substituted tryptophans via a C3- to C2-alkyl migration - Mari, Michele; Lucarini, Simone; Bartoccini, Francesca; Piersanti, Giovanni; Spadoni, Gilberto (Beilstein Journal of Organic Chemistry, 2014)
The reaction of 3-substituted indoles with dehydroalanine (Dha) derivatives under Lewis acid-mediated conditions has been investigated. The formation of 2-substituted tryptophans is proposed to occur through a selective alkylative dearomatization–cyclization followed by C3- to C2-alkyl migration and rearomatization.
Keywords: Dehydroalanine; Friedel–Crafts alkylation; indoles; migration; tryptophans